ENHANCING THE LEGALITY OF SEX EDUCATION TO SAFEGUARD INDONESIAN CHILDREN FROM SEXUAL VIOLENCE - Nursariani Simatupang; Faisal Faisal (Kanun Jurnal Ilmu Hukum, 2022)
Sexual violence against children is an abhorrent act that profoundly impacts their growth and development. To address this issue, the government has a responsibility to educate teenagers about sexual education, as outlined in article 136-137 of Law (UU) Number 36 of 2009, which focuses on Adolescent Health. However, despite these efforts, the prevalence of sexual violence continues to rise. One contributing factor is believed to be the lack of comprehensive sex education for children at an early age. Therefore, it is crucial to provide age-appropriate sex education to children, tailored to their developmental stage. This education aims to empower children to recognize and prevent acts of sexual violence. It includes teaching children about the importance of safeguarding and protecting their private body parts, establishing boundaries, and equipping them with procedures to protect their body and dignity. By implementing such measures, we can strive to create a safer environment for children and reduce the occurrence of sexual violence.